Resumption of meiotic maturation of oocytes, pre- and post-implantation mortality of embryos under ten-time intravenous treatment of silver nanoparticles in mice - Sribna, Valentyna O.; Kaleynykova, Oksana N.; Grushka, Natalia G.; Blashkiv, Taras V.; Voznesenska, Tetyana Yu.; Yanchiy, Roman I. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: In recent years the use of silver nanoparticles (AgNP) has increased significantly being focused on assessing human health and environmental risks of nanotechnology. Methods: Research (two series) has been done on white laboratory mice. One dose (20 mg/kg) has been investigated. Frequency of treatment: one time per day for 10 times. Material for the study (ovaries, tubes and uterus) was taken under anesthetic anesthesia on the 10/11th, 21/22nd, 33/34th, 42/43rd days (after the last treatment). Oocyte meiotic maturation, pre- and post-implantation mortality of embryos under ten-time intravenous treatment of AgNP were investigation. Results: Under the ten-time treatment of AgNPs, the inhibition of reproductive function in female mice occurs: a decrease in the number and quality of ovarian oocytes; after male mice were planted, the females do not get pregnant to 21/22 day. The reproductive function in experimental animals is restored on the 40th day after the last treatment with AgNPs; there is no differences between the values of pre- and post-implantation mortality of embryos on the 33/34th day after male mice were planted; in one of the three experimental animals, 7 live pups were born on the 42/43rd day after the male was planted (in animals of the control group during this period: twice (6 ± 1 (n = 6) live pups). Conclusions: In mice females, under a ten-time treatment of AgNPs, the inhibition of reproductive function takes place; with the termination of the AgNPs treatment, the reproductive function is restored.